Lonto Leok sebagai Filsafat Perdamaian Perspektif Eric Weil dalam Membangun Peradaban Bangsa Indonesia Yang Humanis - Rabim, David; Armada Riyanto, FX. (Humanis; Vol 27 No 4 (2023), 2023)
The phenomena of murder, deprivation of the right to life, racism, and legal injustice often occur in the practical political Indonesian society. This illustrates the nation's moral and ethical decadence. What is the goal of living together, namely peace and prosperity, is absent from the reality of Indonesian Human civilization. Based on the above phenomena, the focus of this research is the lonto leok culture as a philosophy of peace from Eric Weil's perspective in building a humanist Indonesian civilization. The method used is text analysis as well as a phenomenological approach. This means exploring the humanitarian events of the Indonesian nation through the lens of lonto leok culture and Eric Weil's philosophy of peace. The lonto leok culture as local wisdom of the Manggarai people carries a spirit of solidarity based on awareness of the dignity of others as subjects. Each subject in Lonto Leok is a person who puts forward rational discourse aimed at a sense of peace and prosperity. The same thing was also discussed by Eric Weil, namely the philosophy of peace. For him, living peacefully originates from the capacity for rational-relationship. This research thus aims at a dialogue between lonto leok culture and Eric Weil's philosophy of peace in building a more humanistic Indonesian civilization.